Tumor penetration and epidermal growth factor receptor saturation by panitumumab correlate with antitumor activity in a preclinical model of human cancer - Freeman Daniel J; McDorman Kevin; Ogbagabriel Selam; Kozlosky Carl; Yang Bing-Bing; Doshi Sameer; Perez-Ruxio Juan; Fanslow William; Starnes Charlie; Radinsky Robert (Molecular Cancer, 2012)
Abstract Background Successful treatment of solid tumors relies on the ability of drugs to penetrate into the tumor tissue. Methods We examined the correlation of panitumumab (an anti-epidermal growth factor [EGFR] antibody) tumor penetration and EGFR saturation, a potential obstacle in large molecule drug delivery, using pharmacokinetics, pharmacodynamics, and tumor growth rate in an A431 epidermoid carcinoma xenograft model of human cancer. To determine receptor saturation, receptor occupancy, and levels of proliferation markers, immunohistochemical and flow cytometric methods were used. Pharmacokinetic data and modeling were used to calculate growth characteristics of panitumumab-treated tumors. Results Treatment with panitumumab in vivo inhibited pEGFR, Ki67 and pMAPK levels vs control. Tumor penetration and receptor saturation were dose- and time-dependent, reaching 100% and 78%, respectively. Significant tumor inhibition and eradication (p < 0.05) were observed; plasma concentration associated with tumor eradication was estimated to be 0.2 μg/ml. The tumor inhibition model was able to describe the mean tumor growth and death rates. Conclusions These data demonstrate that the antitumor activity of panitumumab correlates with its ability to penetrate into tumor tissue, occupy and inhibit activation of EGFR, and inhibit markers of proliferation and MAPK signaling.